Caracterização sócio-ambiental do Rio Mearim na cidade de Arari-MA - Cunha, Hermeneilce Wasti Aires Pereira (2003)
Study about the socio-environmental characteristics of the river Mearim in the municipal district of Arari-MA, Brazil. An analysis and evaluation of physiochemical and microbiological variables of the water of the river Mearim realized in the period of December of 2002 and March of 2003, as possible indicators of environmental alterations provoked by the inadequate disposition of the waste in the banks of the river. It was verified the release "in natura" of solid and liquid residues in its margins, as well as the ravage provoked by the deforestation and the erosion caused by inadequate agricultural practices. The results of the analysis of the waters in agreement with the CONAMA’s reference values, indicating the need of the rational use of that resource. With respect to the investigation of the life quality of the local population it was noticed through questionnaires of sampling probability no accidental that the population still faces serious problems of social order, being necessary the implementation of public politic programs that incorporate actions to promote the welfare of the community.